Pengaruh Krim Kombinasi Asam Traneksamat 4%, Nikotinamida 3%, Asam Hialuronat 1%, dan Laktobasilus 1% pada Skor MASI Pasien Melasma - Ivani Ivani; Prasetyadi Mawardi; Nurrachmat Mulianto (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Melasma is a chronic recurrent hyperpigmentation disorder characterized by brownish-to-gray facial patches that may negatively affect patients' quality of life. Its multifactorial pathogenesis involves ultraviolet radiation, hormonal influences, genetic predisposition, inflammation, and oxidative stress, highlighting the need for therapies targeting multiple biological pathways. This study aimed to evaluate the effect of a combination cream containing 4% tranexamic acid, 3% nicotinamide, 1% hyaluronic acid, and 1% Lactobacillus on Melasma Area and Severity Index (MASI) scores in patients with melasma. A double-blind randomized controlled trial was conducted in 28 subjects randomly allocated into two groups (combination cream, n=14; modified Kligman's formula, n=14) using computer-generated randomization. The primary outcome was the MASI score, while treatment safety, assessed from local skin reactions, was evaluated as a secondary outcome. Evaluations were performed at weeks 2, 4, 6, and 8 using MASI scores. Pre- and post-treatment analyses were conducted using repeated measures ANOVA and Friedman's test, while between-group comparisons were performed using an independent t-test. The combination cream group demonstrated a reduction in MASI score from 12.90±5.47 to 6.62±3.00 at week 8 (mean change ΔMASI = −6.28) , although statistical significance was not reached (p=0.054). The modified Kligman's formula group showed a significant reduction in MASI score from 13.94 to 7.93 at week 8 (mean change ΔMASI = −6.01) (p<0.001). Comparative analysis demonstrated no significant differences between groups regarding MASI score improvement (p>0.05). Local skin reaction scores were consistently lower in the combination cream group from week 4 to week 8 (all p≤0.004). The combination cream showed a trend toward MASI improvement that did not differ significantly from the modified Kligman's formula, with a more favourable tolerability profile